Modeling world Englishes from the perspective of language contact. Issue 2 (June 2016) - ONYSKO, ALEXANDER
ABSTRACT: Research into world Englishes has continued to expand and diversify since the publication of foundational studies in the late 1970s and early 1980s. From then on, the question of how to model the plurality of Englishes has inspired a range of answers given in different theoretical models. After tracing some of the major approaches to classifying the diversity of Englishes in the world, this paper explores the notion of language contact as an underlying mechanism for all Englishes. A model of language contact is developed, which forms the background for proposing the Language Contact Typology (LCT) of world Englishes. The LCT offers a new way of categorizing Englishes, providing an alternative framing to existing models in the field. It also bears some implications on the controversial notion of 'native speaker' in the world Englishes paradigm.